Can Financial Technology Drive Economic Growth in Indonesia? - Eogenie Lakilaki; Annisa Syaqbania; Rizki Amelia; Septio Pratama Putra; Muhamad; Nia Afriza (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the contribution of fintech to economic growth in Indonesia using a quantitative approach. Fintech, which encompasses digital payment platforms and peer-to-peer lending (P2P) services, has facilitated convenient access to financial resources and enhanced transactional efficiency. However, negative impacts have also been identified, particularly the risk of default and high interest rates, which may impede economic growth. The data employed in this study encompasses the distribution of fintech financing registered with the Financial Services Authority (OJK) from 2018 to 2023, in addition to Indonesia's economic growth data from the Central Statistics Agency (BPS). The analysis findings indicate that while fintech has significant potential in expanding financial inclusion, its adverse effects, such as elevated levels of bad debt and misallocated financing, can impede economic growth.